Identification of commonalities across different languages - Green, Kieran (Frontiers in Language Sciences, 2023)
This work fulfils the need for quantifiable, physical, common characteristics across different languages, which is needed to support the theory that humans use a domain general neurocognitive machinery to acquire, process and produce language. It is shown that four different languages-English, German, Slovak and Japanese-contain linguistic chunks characterised by at least one redundancy, degeneracy, pluripotentiality or modularity (R, D, P & M) trait, following precedent from other fields of signal investigation, with regard to redundancy and resilience from complex systems science. It is first established that language can be regarded as a set of signals between individuals within a complex adaptive systems (CAS) framework, and that all signals in all signalling systems exhibit R, D, P and/ or M traits. It is then shown that linguistic chunks can be regarded as individual signals and that the chunks examined from the aforementioned languages express at least one R, D, P and/ or M trait. The present contribution thereby indicates the potential provision of a new source of data for quantification of some of the pressures involved in language production and processing, and the work concludes by assessing the value of the present work for further investigation in related fields.